2014
DOI: 10.3892/ol.2014.2245
|View full text |Cite
|
Sign up to set email alerts
|

Potential new role of the GHSR-1a-mediated signaling pathway in cardiac remodeling after myocardial infarction (Review)

Abstract: The gastrointestinal hormone ghrelin has important cardiovascular protective effects, however, its specific mechanisms are not yet completely understood. Recent studies have shown that the ghrelin receptor, growth hormone secretagogue receptor type 1a (GHSR-1a), regulates cell proliferation, apoptosis and inflammation-related signaling pathways. In human aortic endothelial cells, ghrelin activates NO production through AMP-activated protein kinase (AMPK) and Akt activation, and these effects can be blocked by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 36 publications
(36 reference statements)
0
13
0
Order By: Relevance
“…Cellular hypoxia causes large numbers of cellular events, resulting in loss of myocardium [24, 25]. Then, ventricular begins to be remodeled gradually, accompanied by fibrosis, chamber enlargement and heart failure [26]. Herein, we employed hypoxia to simulate the process of MI in H9c2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular hypoxia causes large numbers of cellular events, resulting in loss of myocardium [24, 25]. Then, ventricular begins to be remodeled gradually, accompanied by fibrosis, chamber enlargement and heart failure [26]. Herein, we employed hypoxia to simulate the process of MI in H9c2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…In-vitro studies reveal that ghrelin increases the size, prolongs survival and protects the cardiomyocytes and endothelial cells against apoptosis and myocardial injury by stimulating Mitogen-activated protein kinases (p38-MAPK) activity and inhibiting AMP-activated protein kinase (AMPK) activity [ 58 , 59 ]. In human aortic endothelial cells; ghrelin stimulates the production of nitrous oxide (NO) through activation of adenosine monophosphate-activated protein kinase (AMPK) and protein kinase B (Akt) [ 60 ]. Ghrelin system may play a vital role in regulating cardiac remodelling after myocardial infarction [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported that ghrelin can modulate cell physiology and pathophysiology based on an autocrine mechanism through widely expressed unique class of receptors, which are known as Growth Hormone Secretagogue Receptors (GHSRs). These receptors have two known subtypes, GHSR1a and GHSR1b . The GHSR‐1a has been found distributed in vascular endothelium, myocardium, and monocytes .…”
Section: Introductionmentioning
confidence: 99%